The usefulness of indirect calorimetry as a method for measuring resting energy expenditure in acute intestinal failure - Sutuła-Grabowska, Małgorzata; Panasiuk, Anatol (Gastroenterology Review/Przegląd Gastroenterologiczny, 2025)
Medicine is a constantly evolving discipline that uses the latest technologies and devices to support patients effectively according to the most up-to-date standards. Modern technology also enables the individualization of treatment, which is the foundation of personalized medicine. One clinical area where these advancements are applied is in gastrointestinal failure, acute intestinal failure (AIF) in particular. A particularly challenging issue in this field remains the accurate assessment of patients’ caloric needs. This article presents a critical literature review on the potential application of indirect calorimetry (IC) as a method for measuring resting energy expenditure in cases of AIF, especially within internal medicine wards. The review focused on articles published from 1997 to 2024 across various scientific databases. Based on this analysis, it can be concluded that, despite its numerous advantages and proven usefulness in a wide range of clinical settings, indirect calorimetry has certain limitations that significantly impact its applicability in AIF.